(untitled) (Fiep Bulletin - online, 2020)
The Material and Sterilization Center (CME) is a functional unit for processing, Cleaning, sterilization, storage and distributionMultiple items for health. Providing support to all the services of diagnosis and care of a hospital.The aim is to characterize articles that address the importance of nurses in the Material and Sterilization Center and summarize the measures proposed for the proper functioning of your team, as well as reduce possible errors, evidenced in the literature. The search was conducted in electronic MEDLINE, LILACS and BDENF - Nursing and 12 articles were included in the sample. the importance of nursing was evidenced as well as some measures in order to remedy errors, such as: training, continuing education and qualification of this professional. Aiming at the CME as a whole and emphasizing the role of the nurse as a leader and nursing staff within the working process of this unit. The results of the study allowed the identification of some failures in the processing of healthcare products, and identified the importance of nursing at each stage of this process to maintain the sterility of these materials. This work was designed in order to serve as a tool for improving the work process in the CME and can be used as a research tool for professionals and students, for the development of standard operating procedures (SOPs) in institutions, guiding the practices in service through training and continuing education.